Ecotourism lake design: a projective design for the enhancement of social, natural, and economic capital for Cheney State Park - Nichols, Avery (Kansas State University, 2020)
The tourism industry is considered to be one of the largest growing industries in the world, with approximately 700 million international travelers in 2002. Tourism has continued to grow with 1.3 billion travelers in 2017 and earnings around 2.7 trillion dollars (Dossier, 2018). Ecotourism, a subset of the tourism industry is defined as “Responsible travel to natural areas that conserves the environment, sustains the well-being of the local people, and involves interpretation and education” (TIES, 2015). Countries around the world are recognizing the importance of ecotourism, and the economic growth that it brings. To explore how ecotourism can enhance state parks through design, this project focuses on Cheney State Park. There is an opportunity to enhance conditions at Cheney State Park through designing spaces around the lake. Diminishing infrastructure such as trails, campsites, beaches, and overgrown vegetation are some of the concerns at the lake. A lack of funding in the state parks is one of the contributing factors to low maintenance strategies and diminishing infrastructure. Through previous studies, on-site observation, site analysis, and interviews, a projective design will be produced for the site of Cheney State Park in Kansas. The data and research collected will inform sustainable design, and design guidelines for state parks. This research will focus on the development of infrastructure that reflects the local environment and incorporates local natural resources in a sustainable way. From the design of trails, beaches, campgrounds, and open recreation space at Cheney State Park, with the model of existing conditions, aesthetics, and ecology, an effective form of ecotourism will be achieved. From this research, design guidelines will be created to inform the sustainable design of areas within Cheney State Park to be used as a prototype for other state parks in Kansas. Those design guidelines will be created in an effort to bring about ecotourism and design standards to similar state parks in Kansas.
Keywords: Ecotourism; Sustainable; Lake Design; Community; Capitals